Clinical legal education: the challenge of large student numbers - Du Plessis, M. A. (Faculty of Law, University of the Free State, 2013)
Clinician:student ratios in clinical courses at South African university law clinics were found to be, in some instances, more than three times the ratio recommended at other international jurisdictions. Whether clinical legal education should be a mandatory course in the LLB curriculum and whether the focus of the clinicians should be on student training will be probed. In considering the challenge of large student numbers, the solution of grouping students into student law firms for collaborative work will be proposed. The student firm sizes will be discussed and it will be suggested that students work in pairs within student firms. The firm set-up, its operations and the possibility of social loafing will be discussed. It will be shown that the advantages of collaboration far outweigh any disadvantages. Recommendations will be made and it will be shown that the grouping of students in firms will ensure less contact time with clinicians, which will address their workloads and time constraints.

Daar is gevind dat die getalleverhouding tussen kliniese dosente en studente in Suid-Afrikaanse regsklinieke soms so veel as drie keer meer is as die internasionale aanbevole verhouding. Daar sal ondersoek gedoen word na die vrae of die kliniese kursus verpligtend moet wees, asook of die kliniese dosent se fokus op studenteopleiding moet wees. In die aanspreek van die uitdaging van groot studentegetalle, word ‘n oplossing gevind in die groepering van studente in afsonderlike studente-regsfirmas. Die firmas se daarstelling, hul werking en die moontlikheid van sosiale ‘lyfwegsteek’ sal bespreek word. Daar sal aangetoon word dat die voordele van hierdie samewerking baie meer is as enige nadele. Aanbevelings sal gemaak word en daar sal aangedui word dat die groepering van studente in firmas tot minder kontakure met die kliniese dosente sal lei, wat weer hulle werksladings en tydsdruk sal aanspreek.
This article emanated from a paper delivered at the 11th International Journal of Clinical Legal Education Conference and the 12th Australian Clinical Legal Education Conference, 16-18 July 2013, Griffith University, Brisbane, Australia.
Keywords: Clinical legal education; Large student numbers; Student law firms